Behaviour and applications of deployable structure - Tom, Michael. (2010)
This project is aimed to provide a more detailed understanding of a Deployable Structure in terms of its fundamental deploying behaviours through investigation and simulation aided with engineering software ABAQUS 6.7.1, as well as its structural feasibility of daily applications in current and future time. The investigation includes a basic literature patent review of a Retractable Dome invented by Theodore R. Zeigler[2]; including descriptions on the self-interlocking mechanism and one primary interlocking point system which provide the most essential requirement of a Deployable Structure: Stability and Rigidity. The investigation and software simulation was carried out on one deployable joint system extracted from Zeigler’s Retractable Dome[2]. Important aspects such as basic deploying behaviours, program analysis results & discussions covering structural properties such as stresses, deformations, reaction forces and methodology of modelling the deployable joint system are covered in details. Assessments of advantages & disadvantages of the Retractable Dome[2] as well as few other examples of Deployable Structure are also included to provide further perspective of Deployable Structure in efficiency, convenience and economical point of view.